2019
DOI: 10.4110/in.2019.19.e15
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Subsets Are Identified from the Peritoneal Myeloid Mononuclear Cells Expressing both CD11c and CD115

Abstract: To this date, the criteria to distinguish peritoneal macrophages and dendritic cells (DCs) are not clear. Here we delineate the subsets of myeloid mononuclear cells in the mouse peritoneal cavity. Considering phenotypical, functional, and ontogenic features, peritoneal myeloid mononuclear cells are divided into 5 subsets: large peritoneal macrophages (LPMs), small peritoneal macrophages (SPMs), DCs, and 2 MHCII + CD11c + CD115 + subpopulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…Statistical significance of the differential expression data was determined using an independent t-test and fold change in which the null hypothesis was that no difference exists among the groups. False discovery rate (FDR) was controlled by adjusting p value using Benjamini-Hochberg algorithm [44][45][46].…”
Section: Rna Extraction and Rna-sequencing Analysismentioning
confidence: 99%
“…Statistical significance of the differential expression data was determined using an independent t-test and fold change in which the null hypothesis was that no difference exists among the groups. False discovery rate (FDR) was controlled by adjusting p value using Benjamini-Hochberg algorithm [44][45][46].…”
Section: Rna Extraction and Rna-sequencing Analysismentioning
confidence: 99%
“…injection, peritoneal DCs must be responsible for the capture, process, and presentation of Ags to T cells and thus initiating immune responses; however, studies regarding those aspects of peritoneal DCs have been limited. Although recent studies have characterized the diversity of peritoneal DC subsets, the distinct roles between peritoneal cDC subsets are yet to be investigated in depth (25)(26)(27). In the previous study (27), we demonstrated that new subsets of peritoneal DCs and macrophages were identified by differences in their ability to present antigens to and thus stimulate T cells.…”
Section: Introductionmentioning
confidence: 84%
“…Although recent studies have characterized the diversity of peritoneal DC subsets, the distinct roles between peritoneal cDC subsets are yet to be investigated in depth (25)(26)(27). In the previous study (27), we demonstrated that new subsets of peritoneal DCs and macrophages were identified by differences in their ability to present antigens to and thus stimulate T cells. Our present study examines and compares the capabilities of peritoneal cDC subsets regarding their ability to control T cell responses, and we have discovered that peritoneal cDC1s have a dominating role in modulating CD8 T cell responses by upregulating the expression of IL-2.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations